Exploring Genotype by Environment Interactions for Yield and Agronomic Trait Correlations in Black and White Rice Genotypes in Uganda - Nashim Nassanga; Tonny Obua; Emmanuel Amponsah Adjei; Bridget Nayiga; Jimmy Lamo (International Journal of Agronomy)
Evaluating genotypes for stability and high yield (YLD) in rice is crucial for sustainable production and food security, as genotype by environment interactions (GEIs) complicate the selection of superior germplasm for breeding. This study assessed GEI and trait correlations in superior rice genotypes. Seventeen black rice genotypes and seven improved white varieties were tested in a randomized complete block design across three Ugandan environments: Olweny, Kibimba, and Namulonge. Data were collected on YLD, plant height (PH), panicle number (PN), panicle length (PL), spikelet number (SP), 100-grain weight (GW100), grain length (GL), tiller number (TN), grain width (GW), and grain size (GS). Data analyses were based on multivariate (AMMI and GGE biplot) stability parameters while Pearson’s correlation method was used to obtain the association between traits. Significant variances (p<0.001) were found due to genotype, environment, and G × E interaction for all traits. YLD, PH, PN, PL, SP, GW100, and GL were heavily influenced by environmental factors, while TN, GW, and GS were primarily affected by genotypic variation. Olweny was the most effective environment for discriminating and representing rice YLD responses. The genotypes BR-4, KOMBOKA, BR-13, BR-12, BR-15, and NR-4 were identified as superior for grain YLD across all environments. These stable, high-yielding genotypes are valuable for breeding programs. TN and PN were reliable indicators of high YLD. Further multiseason evaluations in farmers’ production systems are recommended for these genotypes before their release as new black rice varieties in Uganda.